The Role of Servant Leadership, School Culture and Supervision System on Teacher Performance Mediated by Teacher Competence and Moderated by Good Scholl Governance - ., Suyanto; Prajanti , Sucihatiningsih Dian Wisika; ., Kardoyo; Handoyo , Eko (Journal of Ecohumanism, 2024)
The research is an observational study aiming to test a model in which the effect of servant leadership as exogenous constructs; school culture and supervision system will affect teacher performance by mediating factor: competency, with oversight moderation variable. If anything, the need for leadership consistency and governance models which described by Inceoglu et al launched differs greatly according to institution of higher education executing research (Indonesian educational context) because how various cultural norms operate in relation to one another impacts teacher efficacy. This study uses a sample that involves different types of schools within Indonesia and applies Partial Least Squares Structural Equation Modeling (PLS-SEM) for the data analysis with focus on measurement properties as well correlations among variables. Results indicate that while effective supervision and governance, servant leadership as well as organizational culture contributes significantly to teaching performance at school; the combination of these elements are needed in nurturing a high-performing education system. Importantly, provision of effective leadership and governance at all levels of the system for ensuring optimum teacher effectiveness is strongly accorded here by this research. Further research is encouraged to investigate these trends and their influence on teacher performance over time using longitudinal methods.